A ultrapassagem na clínica : da captura do desejo no sintoma ao estilismo de si - Siqueira, Patricia Rodrigues de (2010)
This work aims to analyze the passage of serialized lifestyles to the creation of other modes of existence. We support a clinic with an ethical approach toward a self-styling. In this sense, the clinic device would worry about the questioning of the existence and continuous creation of self and worlds.